Perancangan Sistem Informasi Persediaan Obat Berbasis Web di Poliklinik Wyata Guna Bandung - Primasaji, Mohammad Arya; Seliwati,; Muthmainnah, (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The purpose of this study was to overcome the many calculation errors in inventory recording caused by recording the inventory manually, the frequent occurrence of delays in making drug inventory reports caused by the accumulation of incoming goods transaction data and outgoing goods data. The research method that we apply is SDLC (Analyze, Design System, Coding, Testing, and Implementation). Designed using PHP version 7 programming language with CodeIgniter 3 Framework, UI uses Bootstrap 4 and Javascript Library, for the database using Mysql database. While the Navigation Structure is used as the flow of a program and Flowchart is used to represent the flow of work processes between functions. The result of this research is to handle incoming and outgoing goods transactions to produce accurate inventory reports.
Keywords: Applications; E-Archive; Website